Analisis Penjadwalan Pelaksanaan Gedung Pengadilan Negeri Dataran Hunipopu Klas II Menggunakan Metode CPM: Analysis of Scheduling Implementation of the Hunipopu Plain District Court Building Klas II Using the CPM Method - Mila, Wa; Saleh, La Mohamat; Abdin, Maslan (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
A work network is a flow diagram visualization of the sequence, relationships and dependencies of each activity that must be fulfilled to complete the project. The work network describes the project activities that must be carried out, the logical sequence of activities, the dependencies between activities, the timing of activities through the critical path. By planning a work network, an analysis can be carried out on the project completion time schedule, problems that may arise if delays occur, the probability of project completion, the costs required to speed up project completion and so on. This research aims to determine the work that is referred to as the critical trajectory of the implementation of the construction of the Plains Hunipopu Class II District Court Building. This research carries out schedule planning using the CPM method. CPM (Critical path Method) assumes that the activity time is known with certainty so that only one time factor is needed for each activity. The research results show that in scheduling using the Critical Path Method (CPM) there is 1 critical path, namely A, B, C, F, L, P, Q, R (2+4+11+5+5+4+4+4= 39). From the calculation results, it was obtained that the project implementation time was 39 working weeks. Meanwhile, the planned scheduling is 43 working weeks. So it can be concluded that with the CPM method project work is 4 weeks faster with a time efficiency of 9.30%.